Symptomatic left diaphragmatic eventration in a 64-year-old male: a case report and review of management - Mittal, Gyanendra S.; Rahi, Rajeev; Kshirsagar, Mrunal; Singh, Jaskirat; Malhotra, Kashish (International Surgery Journal, 2024)
Eventration of diaphragm, particularly in adults, are rare and often underdiagnosed, especially when symptomatic. This report presents a case of a 64-year-old male with a symptomatic left sided significant Eventration of Diaphragm, characterized by two months of left upper abdominal pain and exertional dyspnea. The patient’s history included an open cholecystectomy performed three to four years prior. Radiological investigations revealed significant eventration of abdominal contents into the left thorax with a contralateral mediastinal shift. The patient underwent surgical intervention through a left subcostal incision extending 2 cm to the right of midline, where the herniated contents were reduced, and the diaphragm was plicated. Post-operative management was successful, with the patient being discharged on the fifth postoperative day. This case emphasizes the importance of timely diagnosis and surgical management of diaphragmatic hernias in symptomatic adults.